Quality of tomato (Lycopersicon esculentum Mill.) as influenced by boron and zinc under different levels of NPK fertilizers - Salam, MA; Siddique, MA; Rahim, MA; Rahman, MA; Saha, MG (Bangladesh Journal of Agricultural Research, 2010)
The study was conducted at the vegetable research farm of the Horticulture Research Centre, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during the period 2006-2007 to investigate the effects of boron and zinc in presence of different levels of NPK fertilizers on quality of tomato. There were twelve treatment combinations which comprised four levels of boron and zinc viz., i) B0Zn0= 0 kg B + 0 kg Zn/ha, ii) B1.5Zn2.0= 1.5 kg B + 2.0 kg Zn/ha, iii) B2.0Zn4.0 = 2.0 kg B + 4.0 kg Zn/ha, iv) B2.5Zn6.0, 2.5 kg B + 6.0 kg Zn/ha and three levels of NPK fertilizers viz., i) 50% less than the recommended NPK fertilizer dose (50% <RD), ii) Recommended NPK fertilizer dose (RD), iii) 50% more than the recommended NPK fertilizer dose (50% >RD). The highest pulp weight (88.14%), dry matter content (5.34%), TSS (4.50%), acidity (0.47%), ascorbic acid (10.95 mg/100g), lycopene content (112.00 μg/100g), chlorophyll-a (41.00μg/100g), chlorophyll-b (56.00 μg/100g), marketable fruits at 30 days after storage (67.48%) and shelf life (16 days) were recorded with the combination of 2.5 kg B+ 6 kg Zn/ha and recommended dose of NPK fertilizers (N= 253, P= 90, and K= 125 kg/ha). Keywords: Quality of tomato; boron and zinc; NPK fertilizer. DOI: 10.3329/bjar.v35i3.6454 Bangladesh J. Agril. Res. 35(3) : 475-488